Hal-Hal Pokok dalam Pembuatan Suatu Kontrak Bisnis - Lisa Fitria Pusphita (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
A contract is an agreement between two or more parties that creates legal rights and obligations to perform or refrain from performing certain actions. In business practice, a contract serves as a legal instrument that ensures certainty, fairness, and protection for all parties involved. To regulate these legal relationships, a comprehensive understanding of contract law is required as the juridical foundation for drafting and executing agreements. A valid contract must not only fulfill formal and material requirements as stipulated in the Civil Code but also be based on several fundamental legal principles, including the principle of freedom of contract, consensualism, pacta sunt servanda, good faith, and personality. Moreover, the contract formation process consists of several stages: the pre-drafting stage, the drafting stage which involves the structure and anatomy of the contract, and the post-drafting stage which focuses on the implementation and evaluation of the agreement. In its execution, disputes may arise; therefore, appropriate dispute resolution mechanisms such as negotiation, mediation, arbitration, or litigation are essential. A comprehensive understanding of these principles and stages in business contract formation is crucial to ensure that every agreement created is valid, fair, and effective for all parties.